(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The most important element constituting the basis for the functioning of the modern economy of Russia and ensuring the ongoing development of market relations is the competition, understood in a broad sense as a process of rivalry between economic agents, leading to a change in product handling conditions on the relevant market. 2015 was held in Russia under the influence of a number of factors, which contain signs of an economic crisis, which is a condition that affects the development of key segments of the domestic economy and determines Russian policy. Mutual sanctions from the European Union and Russia have caused some changes not only in the economy of the country as a whole, but also in the economy of its individual regions. The Russian economy was faced with the need for a very short time to make a leap in increasing the competitiveness of its products, as well as import substitution, which would normally take many years. In such conditions, the key role of the state is to support not only large branches of the economy and the defense sector, but also to develop a strategy for developing competitive relations in the sphere of small and medium-sized businesses. The article examines the main problems of ensuring Russia’s competitiveness, the reasons for the low efficiency of the national innovation system.